2011
DOI: 10.1177/0961203310395052
|View full text |Cite
|
Sign up to set email alerts
|

Task Force on Catastrophic Antiphospholipid Syndrome (APS) and Non-criteria APS Manifestations (II): thrombocytopenia and skin manifestations

Abstract: The objectives of the 'Task Force on Catastrophic Antiphospholipid Syndrome (APS) and Non-criteria APS Manifestations' were to assess the clinical utility of the international consensus statement on classification criteria and treatment guidelines for the catastrophic APS, to identify and grade the studies that analyze the relationship between the antiphospholipid antibodies and the non-criteria APS manifestations, and to present the current evidence regarding the accuracy of these non-criteria APS manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 70 publications
2
72
3
4
Order By: Relevance
“…Patients with APS may have a broader spectrum of clinical and laboratory manifestations other than stated in those criteria [5], and among various hematologic pathologies described, thrombocytopenia has the leading frequency of occurrence reported in 20-50 % of patients with APS [6]. It is interesting that in some cohorts, the incidence of this non-criteria finding has been reported to be higher than that of criteria findings, and therefore has deserved sufficient attention to be proposed as a part of preliminary classification criteria [7].…”
Section: Introductionmentioning
confidence: 98%
“…Patients with APS may have a broader spectrum of clinical and laboratory manifestations other than stated in those criteria [5], and among various hematologic pathologies described, thrombocytopenia has the leading frequency of occurrence reported in 20-50 % of patients with APS [6]. It is interesting that in some cohorts, the incidence of this non-criteria finding has been reported to be higher than that of criteria findings, and therefore has deserved sufficient attention to be proposed as a part of preliminary classification criteria [7].…”
Section: Introductionmentioning
confidence: 98%
“…Occurrence of thrombosis has been reported in 0% to 71% (mean 21%) of ITP patients with aPL [71]. These results suggest that aPL itself may not be sufficient to trigger TEEs.…”
Section: Comorbidities Of Itp As a Possible Risk Factor For Thromboemmentioning
confidence: 96%
“…Antiphospholipid antibodies (aPL) and thromboembolism in ITP patients: A study that summarized data from 9 published series reported that 25-75% (mean 43%) of ITP patients were positive for aPL [71]. aPL includes anticardiolipin antibodies (aCL), anti-ß2-glycoprotein 1 antibodies, and lupus anticoagulant (LA).…”
Section: Comorbidities Of Itp As a Possible Risk Factor For Thromboemmentioning
confidence: 99%
“…The most common manifestation is livedo reticularis, which presents as persistent purplish, reddish or bluish lesions, maybe showing a mottled aspect, is irreversible with reheating, and generally affects the trunk, arms, and legs. Besides livedo, cutaneous ulcerations, purpuras, ecchymoses, subungual hemorrhages may also be present (6,15,16) .…”
Section: Discussionmentioning
confidence: 99%